GUI Design for Comparative Output Signal DFT and DTFT with LabVIEW - Dwi Astharini; Tsaura Aulia; Putri Wulandari; Rahmat Alamtaha; Rifqy Afisha (Universitas Lampung, 2019)
An application GUI (Graphical User Interface) is designed as a software simulation to compare the output signal of DFT and DTFT. DFT (Discrete Fourier Transform) and DTFT (Discrete Time Fourier Transform) are part of the digital signal processing. Digital signal processing is an analog signal processing method uses a mathematical technique to perform a transformation or retrieving information in digital form. One of the benefits of digital signal processing is to facilitate the representation of the signal, because the signal in digital form will be more visible, easily processed and has high accuracy. This GUI application designed using LabVIEW from National Instruments. LabVIEW is a software graphical programming or a block diagram. LabVIEW program known as VI or Virtual Instrument. The input signal in this application is a square signal